Analisis Kemampuan dalam Pengimplementasian Matriks di Sekolah Menengah Kejuruan - Lukman Wildani; Pebri Yolanda; Satria Agung Laksana; edi supriyadi (Papanda Journal of Mathematics and Science Research, 2022)
This study aims to describe the mathematical comprehension ability of students in class XI of SMK, particularly on matrix material. This research is qualitative descriptive research. The data source obtained was derived from test results, interviews, and documentation. From the research conducted can be it is concluded that the results of students' mathematical comprehension ability on matrix material are included in the low (a)category. the research has shown that there are categories of students' mathematical comprehension ability, namely: students with mathematical comprehension ability in the high category totaled 1 person or 7.69%; (b) Students with mathematical comprehension ability in the medium category totaled 5 people or 38.46%; (c) Students with mathematical comprehension ability in the low category totaled 7 people or 53.84%. As for abilities, the highest mathematical understanding is found in the indicator of re-expressing a concept